(untitled) (Journal of history, 2023)
This article is devoted to the consideration and analysis of modern foreign historiography on the issue of Spiritual and Knightly Orders and Crusades. The purpose of the article is a historiographical review of modern works by foreign authors, both articles, monographs and dissertations, and collections of conference papers devoted to this issue and analysis of the main recent trends in the study of Spiritual and Knightly Orders and their role in the Crusades, which influenced not only the further medieval history of Western Europe, but the World history, up to the present day. This topic, despite its seeming ordinariness and study, is revealed every time from a new side and the problem of the relationship between the West and the East is not so much militarized as cultural and socio-economic, the role of women in the Orders, since the gender issue, previously practically untouched, is today one of the most important in the study of this problems, as well as the role of church propaganda, ideology and changes in the mentality of medieval Western European society, the formation of the ideal of chivalry, all this is relevant at the present stage of the development of international relations in the historical context. The article uses comparative-historical, retrospective and historical-critical methods, as well as cognitive and interdisciplinary methods that allow us to consider the main trends of modern foreign historiography. Keywords: Crusades, spiritual and knightly orders, gender history, Templar Order, Hospitaller Order, papal bulls, Middle Ages